COMPARATIVE ANALYSIS OF FINANCE FUNCTIONING OF RUSSIAN AND OVERSEAS FOOTBALL CLUBS - A. A. Aliev; O. V. Litvishko; D. V. Vyprikov (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
In market economy finance management is one of the most important aspects of any company functioning, which binds different lines of its work and shows the company standing on market, its competitiveness, prospects of sustainable development and value growth. Application of principles, methods and tools in management of finance resources of sport industry entities depends on organizational and legal structure, sources of financing and founders. Criteria of efficiency estimation can be formed by indicators based on the current concept of value oriented approach as well as indicators connected with conventional approaches based on the account model of management, such as profitability, liquidity and sustainability. The authors provide a comparative analysis of finance activity of certain Russian and overseas football clubs in order to assess efficiency of their management and availability of optimum conditions of their functioning. The article shows that in conditions of low popularity ofsports in our country and poor paying capacity of the population in comparison with industrial countries our sports clubs have low finance factor in contrast to their competitors on the international arena. It can be explained by the fact that conditions of clubs’ passing over to the market model of functioning have not been formed yet, which makes them orient to budget sources of financing, while leading European clubs are competent participants of market economy that can work all over the world.